Penerapan Model Pembelajaran Project Based Learning dengan Pendekatan Kontekstual - Luma, Sani Listian; Makahinda, Tineke; Umboh, Sixtus Iwan (Charm Sains: Jurnal Pendidikan Fisika, 2022)
This research was carried out to determine the application of project-based learning models with contextual approaches to the material of the equilibrium of rigid objects to student learning outcomes. The method used in this study is an experiment with the design of one grub pretest-posttest design. The research sample amounted to 25 learners. The data analysis in this study used SPSS 25. From the results of the data analysis obtained an average pretest value of 30.55 and a posttest value of 91.29. The results of the hypothesis test using the Test-t paired sample test obtained a sig value. (2-tailed) is 0.000<0.05. So the data shows that there is an increase in student learning outcomes using a project-based learning model with a Contextual approach. Thus it can be concluded that the average score of the results of learning physics learners who are given treatment by using the application of project-based learning models with a contextual approach is higher than the average physics learning outcome when not given treatment.